2009
DOI: 10.1534/genetics.107.084392
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chromosome Ends in the Filamentous FungusNeurospora crassa

Abstract: Telomeres and subtelomere regions have vital roles in cellular homeostasis and can facilitate niche adaptation. However, information on telomere/subtelomere structure is still limited to a small number of organisms. Prior to initiation of this project, the Neurospora crassa genome assembly contained only 3 of the 14 telomeres. The missing telomeres were identified through bioinformatic mining of raw sequence data from the genome project and from clones in new cosmid and plasmid libraries. Their chromosomal loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 74 publications
(83 reference statements)
4
58
0
Order By: Relevance
“…This approach allowed our group to map 19 out of the 22 chromosome ends expected in its linkage map (Perez et al, 2009), as well as to study the telomere adjacent regions. Similar strategies have been described by different authors (Rehmeyer et al, 2006;Sanchez-Alonso & Guzman, 2008;Wu et al, 2009). The search for telomere regions was performed in whole genome sequence draft assemblies.…”
Section: Fungal Telomeres -A Bioinformatics Approachsupporting
confidence: 62%
See 4 more Smart Citations
“…This approach allowed our group to map 19 out of the 22 chromosome ends expected in its linkage map (Perez et al, 2009), as well as to study the telomere adjacent regions. Similar strategies have been described by different authors (Rehmeyer et al, 2006;Sanchez-Alonso & Guzman, 2008;Wu et al, 2009). The search for telomere regions was performed in whole genome sequence draft assemblies.…”
Section: Fungal Telomeres -A Bioinformatics Approachsupporting
confidence: 62%
“…This sequence has been described in Aspergillus nidulans (Bhattacharyya & Blackburn, 1997), Beauveria bassiana (Padmavathi et al, 2003), Botrytis cinerea (Levis et al, 1997), Cladosporium fulvum (Coleman et al, 1993), Fusarium oxysporum (Inglis et al, 2000), Glomus intraradices (Hijri et al, 2007), Magnaporthe grisea (Gao et al, 2002), Metarrhizium anisopliae (Inglis et al, 2005), N. crassa (Wu et al, 2009), Pestalotiopsis microspora (Long et al, 1998), Pleurotus ostreatus (Perez et al, 2009), Pneumocystis carinii (Keely et al, 2001), and Ustilago maydis (Sanchez-Alonso & Guzman, 2008). However, variations of this sequence can be found in other fungi such as A. oryzae that has dodecanucleotide telomere repeats (Kusumoto et al, 2003) Incomplete and imperfect telomere units have been reported in: A. oryzae, Candida albicans, Kluyveromyces lactis, S. cerevisiae and S. pombe.…”
Section: Fungal Telomeres -A Bioinformatics Approachmentioning
confidence: 88%
See 3 more Smart Citations